Vermicompostagem e desenvolvimento inicial de alface em doses superiores de Trichoderma - Wiethan, Maria Medianeira Saccol (2015)
Pesticide use reduction is one of the alternatives usedin organic agriculture. Pesticides may bereplaced by biological agents, which are less harmful to the environment. SomeTrichoderma isolates are considered to be important and efficient biological agents. They protect plants from plant diseases when used at optimal doses and have mechanisms to enable seed germination and vegetable development. Few studies evaluate seed germination and plant development interaction with vermicomposting at highTrichoderma doses. Thus, the current study aims to test higher doses of the ICB Nutrisolo Trichoderma (ICB) biological commercial product than the recommended ones. It was done by evaluating, Eisenia andrei multiplication and development, the changes in the substrate s chemical features as well as the emergence and the initial development of lettuce seedlings in vermicompost. Regarding experiment 1, E. andrei multiplication and development, the experimental unit consisted of 6 kg of cattle manure in boxes containing 48 E. andrei earthworms. ICB commercial product doses of 0,0; 0,5; 1,0; 2,0; 4,0 and 8,0 were used at the concentration of 1011 CFU kg-1 in the substrate. The treatment without earthworms was also conducted to evaluate the vermicompost chemical features. The number of adult and young earthworms and of earthworm cocoons was counted, and the total dry weight was evaluated. As for experiment 2, which was conducted in greenhouse, the substrate was a mixture of vermicompost and commercial substrate at the ratio 1:1 (v/v). ICB doses of 0,0; 1,0; 2,0; 4,0; 8,0 and 16,0 were used at concentration of 1011 UFC kg-1 in the substrate. The inoculated substrate was placed in germination trays. Each experimental unit was composed of 10 cells, and each cell received five Regina cultivar lettuce seeds. After the seedlings emerged, a thinning was conducted by leaving one seedling per cell. The evaluated variables were germination percentage, seedling emergence speed index, height, shoot fresh and dry weight, leaf area, root volume and surface area, and P, K, Ca and Mg percentages in the leaves. The experimental designs were randomized with four replications. There was decrease in the number of earthworms when ICB doses equal to or above 4,0 were used. Doses up to 1,0 did not change the number of adult E.andrei earthworms and cocoons. However, the multiplication index was lower in all ICB treatments and doses above 2,0 decreased the total dry weight. The pH was higher in ICB treatments, and there was increased P, K and Mg percentage in the presence of earthworms. The doses studied in experiment 2 negatively influenced the plants shoot and root development. The germination percentage and the seedling emergence speed index were negatively influenced when doses above 4,0 were used. The leaf chemical analysis showed that all doses increased the percentage of analyzed nutrients.